GAMBARAN TINGKAT STRES PADA LANSIA YANG TINGGAL DI PANTI WERDHA TRESNA BUDI PERTIWI KOTA BANDUNG (UPPM. Poltekkes Kemenkes Bandung, 2021)
The background of this study is that an elderly person is 60 years or older. Someone who enters the elderly will experience limitations where he will be more dependent on others, the process of making a living stalled and difficult to interact widely. So that some people assume that the elderly are better cared for in an orphanage, because they will be more cared for and able to get along with other elderly people than staying at home alone feeling lonely and abandoned because their children are busy with their work. Stress in the elderly can be influenced by their roommates who has a different culture or are jealous of their roommates who are often noticed by the management of the orphanage and rarely visited by family. The purpose of this study was to determine the description of stress levels in the elderly who live in the Nursing Home of Tresna Budi Pertiwi Bandung. The method used is descriptive design with 22 elderly population. Samples were taken by Total Sampling, while the number of samples taken was 20 respondents in accordance with the inclusion criteria set by researchers. The results showed that most were experiencing moderate stress and almost half were experiencing mild stress. For the management of the nursing home, wherda can guide and motivate the elderly so they do not experience prolonged stress. Keywords: Stress, Elderly, Nursing Home, Bibliography 49. (2002-2019)